Method of Extracting The Choroidal Area and Its Quantitative Analysis on Optical Coherence Tomography Images for the Diagnostics of Eye Diseases - Demin, N. S.; Ilyasova, N. Yu; Samigullin, R. T. (Journal of computer & systems sciences international, 2024)
This paper proposes a technology for the extraction of the vascular tissue of the human eye and calculation of the choroidal vascular index on optical coherence tomography (OCT) images. The choroid is one of the most vascularized structures of the human body and plays an indispensable role in the nutrition of photoreceptors. The applied approach is based on the use of the method of shadow compensation of OCT images with their subsequent filtering and binarization. The technology for isolating the choroidal region and quantitatively assessing the choroidal vascular index (CVI) on OCT images to identify endocrine ophthalmopathy (EOP) is considered. This technology has made it possible to automate the calculation of choroidal vascular index value, which is an important indicator in the study of the vascular layer when diagnosing eye diseases.